2004
DOI: 10.1088/1126-6708/2004/03/012
|View full text |Cite
|
Sign up to set email alerts
|

Lower limit on the neutralino mass in the general MSSM

Abstract: We discuss constraints on SUSY models with non-unified gaugino masses and R P conservation. We derive a lower bound on the neutralino mass combining the direct limits from LEP, the indirect limits from (g − 2) µ , b → sγ, B s → µ + µ − and the relic density constraint from WMAP. The lightest neutralino mχ0 1 ≈ 6 GeV is found in models with a light pseudoscalar with M A < 200 GeV and a large value for tan β. Models with heavy pseudoscalars lead to mχ0 1 > 18(29) GeV for tan β = 50(10). We show that even a very … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 140 publications
(112 reference statements)
1
76
0
Order By: Relevance
“…For µ < 0, we again found that the Likelihood of the points is much smaller than for µ > 0, owing mainly to the (g − 2) µ constraint which disfavours large values of tan β as well as low values of M 2 and ml [15].…”
Section: Fig 5: Same As Inmentioning
confidence: 67%
See 1 more Smart Citation
“…For µ < 0, we again found that the Likelihood of the points is much smaller than for µ > 0, owing mainly to the (g − 2) µ constraint which disfavours large values of tan β as well as low values of M 2 and ml [15].…”
Section: Fig 5: Same As Inmentioning
confidence: 67%
“…1 represents Q/Q max , the weigth normalized to the best weight, with respect to the free parameters that we have considered. The first plot shows that the bino mass is peaked around M 1 ∈ [15,19] GeV while the second plot shows that µ is below 150 GeV. That is, it is near the lower bound that satisfies the LEP limits on charginos.…”
Section: A Neutralino Masses Smaller Than 15 Gevmentioning
confidence: 93%
“…For early works addressing limits on light neutralino Dark Matter, see e.g. [11][12][13], and for limits on (very) light neutralinos without cosmological bounds we refer to refs. [14,15] and references therein.…”
Section: Jhep11(2014)106mentioning
confidence: 99%
“…Assuming R-parity conservation, the neutralino is stable and a good dark matter candidate. Accelerator searches and relic density constraints from WMAP data allow a lower limit to be set on the mass of the MSSM neutralino [4]. Typical lower limits for m χ 0 1 from such studies lie around 20 GeV, depending on the values chosen for tanβ, the ratio of the vacuum expectation values of the two neutral Higgses.…”
mentioning
confidence: 99%